Regulatory T cells in the peripheral blood of women with gestational diabetes: a systematic review and meta-analysis - Arain, Hania; Patel, Tina; Mureanu, Nicoleta; Efthymiou, Athina; Lombardi, Giovanna; Tree, Timothy; Nicolaides, Kypros H.; Shangaris, Panicos (Frontiers in Immunology, 2023)
Background Gestational diabetes (GDM) affects approximately 14% of pregnancies globally and is associated with short- and long-term complications for both the mother and child. In addition, GDM has been linked to chronic low-grade inflammation with recent research indicating a potential immune dysregulation in pathophysiology and a disparity in regulatory T cells. Objective This systematic review and meta-analysis aimed to determine whether there is an association between GDM and the level of Tregs in the peripheral blood. Methods Literature searches were conducted in PubMed, Embase, and Ovid between the 7th and 14th of February 2022. The inclusion criteria were any original studies published in the English language, measuring differentiated Tregs in women with GDM compared with glucose-tolerant pregnant women. Meta-analysis was performed between comparable Treg markers. Statistical tests were used to quantify heterogeneity: τ2, χ2, and I2. Study quality was assessed using a modified version of the Newcastle-Ottawa scale. Results The search yielded 223 results: eight studies were included in the review and seven in the meta-analysis (GDM = 228, control = 286). Analysis of Tregs across all trimesters showed significantly lower Treg numbers in women with GDM (SMD, −0.76; 95% CI, −1.37, −0.15; I2 = 90%). This was reflected in the analysis by specific Treg markers (SMD −0.55; 95% CI, −1.04, −0.07; I2 = 83%; third trimester, five studies). Non-significant differences were found within subgroups (differentiated by CD4+FoxP3+, CD4+CD127−, and CD4+CD127−FoxP3) of both analyses. Conclusion GDM is associated with lower Treg numbers in the peripheral maternal blood. In early pregnancy, there is clinical potential to use Treg levels as a predictive tool for the subsequent development of GDM. There is also a potential therapeutic intervention to prevent the development of GDM by increasing Treg populations. However, the precise mechanism by which Tregs mediate GDM remains unclear. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42022309796.